2021
DOI: 10.1111/maec.12638
|View full text |Cite
|
Sign up to set email alerts
|

Composition and diversity of prokaryotic communities sampled from sponges and soft corals in Maldivian waters

Abstract: Coral reefs are one of the most productive and diverse marine ecosystems on the planet and harbour a wide array of taxa including hard and soft corals, sponges, fishes and other invertebrate species. In addition to these large taxa, coral reefs also provide habitat for a range of distinct microbial communities in the abiotic environment (seawater and sediment) and living in symbiosis with the above-mentioned

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 89 publications
0
2
0
Order By: Relevance
“…In the present study, Chloro exi were the most abundant overall bacterial phylum and were only rare in species from the high light intensity pools or adjacent coral reef habitat, namely, the phototrophic species or S. carteri, a known LMA sponge species. A number of studies have found Chloro exi members to be particularly abundant in HMA species (Schmitt et Cleary et al 2020Cleary et al , 2021. Although Chloro exi members are absent or rare in many LMA species, they can be abundant in others.…”
Section: Sar202 Were Enriched In Cave Spongesmentioning
confidence: 99%
“…In the present study, Chloro exi were the most abundant overall bacterial phylum and were only rare in species from the high light intensity pools or adjacent coral reef habitat, namely, the phototrophic species or S. carteri, a known LMA sponge species. A number of studies have found Chloro exi members to be particularly abundant in HMA species (Schmitt et Cleary et al 2020Cleary et al , 2021. Although Chloro exi members are absent or rare in many LMA species, they can be abundant in others.…”
Section: Sar202 Were Enriched In Cave Spongesmentioning
confidence: 99%
“…2013; Bonder et al 2016; Goodrich et al 2016; Gri ths et al 2019; Easson et al 2020; Greenwood et al 2021;Zhang et al 2023). Sponge studies have also shown that host identity is one of the most important determinants of variation in sponge microbiome studies(Thomas et al 2016;Cleary et al , 2020Cleary et al , 2021.Thomas et al (2016), however, noted that sponge phylogeny only explained a minor amount of the variation in dissimilarity of spongeassociated prokaryotic communities. We attribute this to the apparent power law relationship between host dissimilitude and prokaryotic dissimilarity.In contrast to space and host dissimilitude, the purely environmental component only explained a very small amount of variation in composition, 0.3%.…”
mentioning
confidence: 99%